2015
DOI: 10.2139/ssrn.2564094
|View full text |Cite
|
Sign up to set email alerts
|

What is an Emerging Technology?

Abstract: There is considerable and growing interest in the emergence of novel technologies, especially from the policy-making perspective. Yet as an area of study, emerging technologies lacks key foundational elements, namely a consensus on what classifies a technology as 'emergent' and strong research designs that operationalize central theoretical concepts. The present paper aims to fill this gap by developing a definition of 'emerging technologies' and linking this conceptual effort with the development of a framewo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
160
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(169 citation statements)
references
References 111 publications
3
160
0
6
Order By: Relevance
“…The Multi-level Perspective (Rip and Kemp, 1998;Geels, 2005a;Grin et al, 2010) focuses on explaining large scale and long-term shifts -often 50 years or more -from one socio-technical system to another. Examples of transitions include shifts from horse-drawn carriages to automobiles (Geels, 2005b), from manual to mechanized transshipment in harbors (van Driel and Schot, 2005), from mixed farming to intensive pig husbandry (Geels, 2009), and from fossil fuel based energy system to one based on renewables (Verbong and Geels, 2007).…”
Section: The Multi-level Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…The Multi-level Perspective (Rip and Kemp, 1998;Geels, 2005a;Grin et al, 2010) focuses on explaining large scale and long-term shifts -often 50 years or more -from one socio-technical system to another. Examples of transitions include shifts from horse-drawn carriages to automobiles (Geels, 2005b), from manual to mechanized transshipment in harbors (van Driel and Schot, 2005), from mixed farming to intensive pig husbandry (Geels, 2009), and from fossil fuel based energy system to one based on renewables (Verbong and Geels, 2007).…”
Section: The Multi-level Perspectivementioning
confidence: 99%
“…The detection and patterning of these ruptures and continuities invites methodological experimentation, e.g. the use of phylogenetic methods (Mesoudi, 2011;Valverde and Solé, 2015), Big Data analytics (Manning, 2013) or scientometric techniques (Rotolo et al, 2015). In particular, a quantitative mapping of patterns in the evolution of rules and meta-rules is a promising research avenue as both MLP and TEP literatures have so far identified regimes and techno-economic paradigms on the basis of qualitative interpretation of historical data, resulting in a certain lack of analytical rigour.…”
Section: Deep Transitions and The Future: Bottom-up Vs Top-down Tranmentioning
confidence: 99%
“…Returning to auxiliary range extenders, these have developed in the context of EVs as an emerging technology which requires complementary products and services in order to function efficiently. There is no clear consensus on what constitutes an emerging technology but they are characterised by radical novelty, quick growth, coherence, strong impact, uncertainty and ambiguity (Rotolo et al, 2015). The phenomenon of 'range anxiety' suggests that the development of a complementary charging infrastructure is required for EVs to achieve a greater level of consumer acceptance.…”
Section: Range Extenders As Range Adaptionmentioning
confidence: 99%
“…Contributors to this special section further contextualize blockchains as evolving within the type of ambiguous experimentation that more generally characterizes emergent technologies (Einsiedel 2009;Rotolo et al 2015). Eschewing the elaboration of typologies advancing particular features of technology as inherent or fixed (for example, European Central Bank 2015; Swan 2015), Rodima-Taylor and Grimes reveal how blockchains continuously develop in 'heterogeneous networks' with public or private features that are difficult to precisely pinpoint.…”
Section: What Are Blockchains?mentioning
confidence: 99%